Eisenhower - Wukovits, John (Great generals series, 2006)
In the third installment of this series, World War II expert Wukovits explores Dwight D. Eisenhower's contributions to American warfare, and skillfully demonstrates how Eisenhower's evolution as a commander, his military doctrine, and his diplomatic skills are of extreme importance in understanding modern warfare.